PERKEMBANGAN DAN KONTRIBUSI SUBSEKTOR PERIKANAN TERHADAP PDRB KABUPATEN ROKAN HILIR, RIAU - Ramli, M. (Fakultas Perikanan dan Kelautan Universitas Riau, 2013)
The study aims to assess the development and fisheries subsector contribution tothe economy (GDP) Rokan Hilir district. In order to achieve these objectives, the an-nual data collected (series) GDP and fisheries data Rokan Hilir district during the peri-od 2006 to 2010. Based on these data, the fisheries sector contributed 21.62%. Andseen his contribution to the fellow agriculture, fisheries subsector is the largest contrib-utor (41%) among the other sub-sectors (crops and hotikultura, tree crops, livestock,and forestry). Fisheries in Rokan Hilir district dominated by fishing in the ocean. Fish-eries production in 2010 was recorded 59808.43 tons, up from the previous years pro-duction. The increase in production occurred primarily in aquaculture production.